Preparation of transparent conductive multilayered films using active pentafluorophenyl ester modified multiwalled carbon nanotubes - Park, Hye Jin; Kim, Junkyung; Chang, Ji Young; Theato, Patrick (AMER CHEMICAL SOC, 2008)
A mutilayered film was prepared by layer-by-layer (LBL) assembly of active ester modified multiwalled carbon nanotubes (MWCNTs) and poly(allylamine hydrochloride) (PAH). For this purpose, carboxylic groups on the surface of the oxidized MWCNTs were converted to the acyl chlorides by their reaction with thionyl chloride. Subsequent reaction of the acyl chlorides with pentafluorophenol formed the active esters. These active ester modified MWCNTs (MWCNTs-COOC6F5) were air-stable and moisture resistant, but showed a high reactivity toward primary or secondary amines resulting in amide bonds. For the preparation of a multilayered film, the surface of a quartz slide was first activated and sacrificial double layers of PAH and poly(sodiurn 4-styrene sulfonate) (PSS) were deposited. Subsequently, LBL assembly of MWCNTs-COOC6F5 and PAH was then conducted on these double layers [(PAH/PSS)(2)]. In the process of the assembly, a reaction occurred between the active ester on the surface of MWCNTs and the amine groups of polyallylamine yielding amide bonds, which resulted in a mechanically stable thin film. A free-standing film was obtained after dissolving the sacrificial layer [(PAH/PSS)(2)] in a concentrated aqueous NaOH solution. The surface resistance of the multilayered film with 20 bilayers decreased to around 10 kQ while remaining a reasonable transparency (70% at 500 nm).
Keywords: LANGMUIR-BLODGETT-FILMS; BY-LAYER DEPOSITION; FUNCTIONALIZATION; NANOASSEMBLIES